INTERVENSI SCAPULAR RETRACTION EXERCISE DAN NEUROMUSCULAR TAPING UNTUK KOREKSI POSTUR PADA KONDISI UPPER CROSS SYNDROME - Toto Marzuki; Yose Rizal; Syabina Suliza Putri (Jurnal Ilmiah Fisioterapi, 2026)
Background: Upper Cross Syndrome (UCS) is a postural deformity characterized by muscle imbalance, involving tension in the pectoralis major, upper trapezius, and levator scapulae muscles, along with weakness in the deep neck flexors, middle-lower trapezius, and serratus anterior. This condition is frequently triggered by prolonged use of electronic devices, leading to neuromuscular imbalance and musculoskeletal disorders. Objective: This study aims to determine the effect of Scapular Retraction Exercise and Neuromuscular Taping (NMT) on correcting shoulder posture in a patient with UCS. Methods: The research design is a single case study of a 19-year-old male student diagnosed with UCS. Data collection involved measuring the Forward Shoulder Angle (FSA). The intervention consisted of 12 treatment sessions conducted over 6 weeks. Results: Following 12 sessions of combined scapular retraction exercises and NMT application, the final evaluation showed a significant increase in the FSA angle from 46° (E0) to 54° (E1). This increase indicates a reduction in shoulder protraction, moving the acromion toward a more posterior position. Conclusion: The integration of Scapular Retraction Exercise and Neuromuscular Taping (NMT) is effective in improving posture in Upper Cross Syndrome patients through the synergy of active muscle strengthening and mechanical muscle relaxation.